An Empirical Study of Factors Affecting Repurchase Intention in Online Store in Indonesia During Pandemi Covid-19 - Adi Susilo Jahja; Saripudin; Rizki Yuniarti; Andyni Yulfanis Aulia Masrifa (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this paper is to understand the repurchase intention of customers in online shopping. The Covid-19 pandemic has caused transactions through online store Tokopedia grew rapidly. Online stores expect an increase in repurchase intention. This study investigates the relationship between perceived benefits (convenience, product selection, and price) and perceived risks (delivery, product performance, return policy and characteristics) on repurchase satisfaction with customer satisfaction as a mediating variable. Data collected from 100 respondents were analyzed using Partial Least Square-Structural Equation Modeling using the SmartPls program. This study shows that customer satisfaction, product selection, price, delivery, product performance, and return policy are significant positive predictors of customer repurchase intention